Respuesta :

the inverse of a function

steps to find the inverse of a function

step 1: replace f(x) with y

step 2: replace all x's with y's and y's with x's

step 3: solve for y

step 4: replace y with [tex]f^{-1}(x)[/tex], the ineverse of f(x) or whatever function name


given [tex]f(x)=9x^2-12[/tex]

step 1: replace f(x) with y

[tex]y=9x^2-12[/tex]


step 2: replace all x's with y's and y's with x's

[tex]x=9y^2-12[/tex]


step 3: solve for y

[tex]x=9y^2-12[/tex]

[tex]x+12=9y^2[/tex]

[tex]\frac{x+12}{9}=y^2[/tex]

[tex]\sqrt{\pm \frac{x+12}{9}}=y[/tex]

[tex]y=\frac{\pm \sqrt{x+12}}{3}[/tex]


step 4: replace y with function name

here's where we just match which one matches [tex]inverse=\frac{\pm \sqrt{x+12}}{3}[/tex]

that would be A

Answer:

the inverse of a function

steps to find the inverse of a function

step 1: replace f(x) with y

step 2: replace all x's with y's and y's with x's

step 3: solve for y

step 4: replace y with , the ineverse of f(x) or whatever function name

given  

step 1: replace f(x) with y

step 2: replace all x's with y's and y's with x's

step 3: solve for y

 

step 4: replace y with function name

here's where we just match which one matches  

that would be A